2008
DOI: 10.1097/brs.0b013e31816454e0
|View full text |Cite
|
Sign up to set email alerts
|

Examining Vertebrobasilar Artery Stroke in Two Canadian Provinces

Abstract: In Saskatchewan, we observed a dramatic increase in the incidence rate in 2000 and there was a corresponding relatively small increase in chiropractic utilization. In Ontario, there was a small increase in the incidence rate; however, chiropractic utilization decreased. At the ecological level, the increase in VBA stroke does not seem to be associated with an increase in the rate of chiropractic utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…However, patients presenting to a hospital with symptoms of stroke and a recent history of visiting a chiropractor may be subjected to a more aggressive workup for VBS, and consequent bias towards increased diagnosis of VBS. 7 Therefore, because diagnostic misclassification in the chiropractic cohort is more likely to result in more claims for VBS rather than fewer, we are confident that our results do not significantly underestimate the risk of VBS stroke in this study population. The results for the chiropractic cohort reflect the risk of stroke following chiropractic spinal manipulation, not that following all clinical encounters with chiropractors, who routinely screen patients for contraindications to spinal manipulation and withhold manipulation from those perceived as being at risk.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, patients presenting to a hospital with symptoms of stroke and a recent history of visiting a chiropractor may be subjected to a more aggressive workup for VBS, and consequent bias towards increased diagnosis of VBS. 7 Therefore, because diagnostic misclassification in the chiropractic cohort is more likely to result in more claims for VBS rather than fewer, we are confident that our results do not significantly underestimate the risk of VBS stroke in this study population. The results for the chiropractic cohort reflect the risk of stroke following chiropractic spinal manipulation, not that following all clinical encounters with chiropractors, who routinely screen patients for contraindications to spinal manipulation and withhold manipulation from those perceived as being at risk.…”
Section: Discussionmentioning
confidence: 60%
“…al., who found that marked increases in the rates of VBS in two Canadian provinces in 2000 were unassociated with increased utilization of chiropractic services. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Adverse events Seven systematic reviews [24,25,28,29,210-213] and seven primary studies [214-220] were identified specifically concerning adverse events of manual therapy. Mild-to-moderate adverse events of transient nature (e.g., worsening symptoms, increased pain, soreness, headache, dizziness, tiredness, nausea, vomiting) were relatively frequent.…”
Section: Resultsmentioning
confidence: 99%
“…Despite some respondent's concerns, current evidence also suggests that chiropractic care is not causally related to serious adverse events, specifically vertebrobasilar artery stroke [15,16]; however, efforts are currently underway to better establish the risks associated with spinal manipulation [17]. Diversity within the chiropractic profession has been previously reported [18,19], and some practitioners have concluded that "for every chiropractor there is an equal and opposite chiropractor" [20].…”
Section: Resultsmentioning
confidence: 99%